Systematic Literature Review: The Influence of Ratings and Reviews on Purchasing Decisions for Dried Fruit Snacks - Wahyuni Zahra Hidayah; Imay Delin Sabtha Dewi; Putri Ayu Salsabillah (PT. Hidayat Muda Intelektual, 2025)
This study has undergone a systematic review of the purchase decision of dried fruit snacks on the shopee e-commerce platform. Digital transformation in the modern era makes changes in consumer behavior in shopping. By conducting a literature search on Google Scholar, we have selected 20 relevant articles. New findings show that the number of publications continues to increase from 2020 to 2025. This research uses the Systematic Literature Review (SLR) method. Through the Systematic Literature Review (SLR) method, this research identifies ten selected journals that are relevant to the topic, published between 2020 and 2025, and discuss specifically the influence of online customer reviews (OCR) and online customer ratings (OCRt) on purchasing decisions. From the results of the analysis, it can be concluded that OCR and OCRt have a positive and significant influence on purchasing decisions, especially in the context of marketplaces such as Shopee. This research shows that public awareness of healthy lifestyles has led to an increase in fruit consumption, including in the form of snacks such as dried fruit snacks. Demand for dried fruit products increases along with practicality, longer shelf life, and nutritional content that is maintained. Based on the analysis of sales data, ratings, and reviews of dried fruit snack products on the Shopee platform, it was found that ratings and reviews have a significant influence on consumer purchasing decisions. Products with high ratings tend to be more trusted by potential buyers, especially if supported by relevant and informative positive reviews.